2020
DOI: 10.1177/0146167219897660
|View full text |Cite
|
Sign up to set email alerts
|

To Help or To Harm? Assessing the Impact of Envy on Prosocial and Antisocial Behaviors

Abstract: Two studies examined how envy influences prosocial and antisocial behavior. In Experiment 1, participants in an envious state (relative to a neutral state) were less helpful: They picked up fewer dropped pencils in their immediate vicinity. We expanded upon these findings by examining how envy affected both helping and harming behavior in a competitive scenario. In Experiment 2, individuals in envious or neutral states assigned puzzle tasks to another student in a prisoner’s dilemma style scenario. Prosocial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
0
13
0
1
Order By: Relevance
“…As outlined in the Introduction, incongruent emotions should negatively predict prosocial behavior, whereas congruent emotions should be positively linked. Correspondingly, malicious envy increases antisocial behaviors, such as hostility (Salovey & Rodin, 1984), harm (Behler et al, 2020; Cohen-Charash & Mueller, 2007), dishonest behavior (Gino & Pierce, 2009), and defecting cooperation (Wobker, 2015). Similar antisocial behavior has been observed for schadenfreude, such as negative word of mouth (Ouwerkerk et al, 2018; Sundie et al, 2009), cheating (Lange & Boecker, 2019), willingness to harm (Cikara et al, 2011), and reduced helping (Schindler et al, 2015).…”
Section: Discussion Of Moderation-of-process Evidencementioning
confidence: 99%
“…As outlined in the Introduction, incongruent emotions should negatively predict prosocial behavior, whereas congruent emotions should be positively linked. Correspondingly, malicious envy increases antisocial behaviors, such as hostility (Salovey & Rodin, 1984), harm (Behler et al, 2020; Cohen-Charash & Mueller, 2007), dishonest behavior (Gino & Pierce, 2009), and defecting cooperation (Wobker, 2015). Similar antisocial behavior has been observed for schadenfreude, such as negative word of mouth (Ouwerkerk et al, 2018; Sundie et al, 2009), cheating (Lange & Boecker, 2019), willingness to harm (Cikara et al, 2011), and reduced helping (Schindler et al, 2015).…”
Section: Discussion Of Moderation-of-process Evidencementioning
confidence: 99%
“…It is not only defined as a state driven by situations but also conceptualized as a personality trait—dispositional envy that describes the chronic feeling of envy in social settings [ 20 , 21 ]. Based on the dual approach of envy, it is considered as benign envy and malicious envy that entail constructive and destructive aspects [ 22 , 23 ]. The key dimensions that determine what kind of envy appears are the appraisal about the deservingness of envied person’s advantage and the perceived control over the situation of envious individuals [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also emphasized the significance of investigating pro-social behavior during the COVID-19 pandemic. Behler et al (2020) suggested that engaging undergraduate students in social work in the U.S motivated them to engage in prosocial behavior. Religious beliefs and the fear of God have also been associated with prosocial behavior among organizational employees in the U.S (Karatas & Canli, 2020).…”
Section: Motivations For Prosocial Behaviormentioning
confidence: 99%
“…Motivations for engaging in pro-social behaviors are numerous. For example, Behler et al (2020) found that an easy task motivated individuals towards prosocial behavior, whereas difficult tasks led to antisocial behavior. Karatas and Canli (2020) reported that God and religion were the most prevalent motivational reasons to donate money.…”
Section: Introductionmentioning
confidence: 99%